1993
DOI: 10.1103/physrevlett.71.879
|View full text |Cite
|
Sign up to set email alerts
|

Observation of field-induced spin-current relaxation in a Fermi liquid

Abstract: We have studied NMR spin echoes in 3 He liquid in a magnetic field #o = 8 T for temperatures T>4.5 mK. The data are analyzed in terms of the Leggett-Rice effect to obtain the transverse spindiffusion coefficient D± (T). For T<20 mK we find that D± is less than measured in earlier experiments at lower Bo. This phenomenon has been predicted for degenerate Fermi systems, due to the phase space created for quasiparticle scattering by spin polarization. The effect we have measured is more pronounced than suggested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
24
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(27 citation statements)
references
References 16 publications
3
24
0
Order By: Relevance
“…Some comments are in order concerning the possible relevance of our findings to experiment. First we note that the available experimental data in weakly polarized 3 He [6] deviate systematically from the naive theoretical fit which uses a single adjustable parameter (T a in [6]) to cover the entire temperature range including both, ξ > 1 and ξ < 1. Much better agreement is obtained by restricting the fit to the ξ ≤ 1 region with an overall prefactor smaller than the one implied by fitting to the value of D in the low field, high temperature regime (we use for the inverse overall prefactor the value A ≈ 7.7 × 10 5 sec/cm 2 K 2 instead of 5.8 × 10 5 sec/cm 2 K 2 as in Reference [6] and for the "anisotropy temperature" T a ≈ 12.5 mK instead of 16.4 mK).…”
Section: Crossover and Low-fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Some comments are in order concerning the possible relevance of our findings to experiment. First we note that the available experimental data in weakly polarized 3 He [6] deviate systematically from the naive theoretical fit which uses a single adjustable parameter (T a in [6]) to cover the entire temperature range including both, ξ > 1 and ξ < 1. Much better agreement is obtained by restricting the fit to the ξ ≤ 1 region with an overall prefactor smaller than the one implied by fitting to the value of D in the low field, high temperature regime (we use for the inverse overall prefactor the value A ≈ 7.7 × 10 5 sec/cm 2 K 2 instead of 5.8 × 10 5 sec/cm 2 K 2 as in Reference [6] and for the "anisotropy temperature" T a ≈ 12.5 mK instead of 16.4 mK).…”
Section: Crossover and Low-fieldmentioning
confidence: 99%
“…As can be shown by analysing the eigenvalue spectrum of the relaxational part of the collision integral I rel1 [f ] the spin current decays to its steady state value in a microscopic time scale, τ ⊥ , beyond which the time derivative terms in equations (5)(6) can be omitted. In addition, since ∂ M ⊥ (x)/∂x = const or equivalently ∂g/∂x is independent of x, equation (6) implies ∂f /∂x = 0.…”
mentioning
confidence: 99%
“…Using the data of Candela et al, 7 the corresponding apparent anisotropy temperature would be 3 mK in pure 3 He at 8 T, which is much smaller than the value of 16 mK reported in Ref. 16.…”
Section: Comment On Existing Nmr Datamentioning
confidence: 71%
“…In terms of anisotropy temperature, such a saturation value of the spin rotation parameter would correspond to an apparent T a of 9 mK for 6.4% 3 He-4 He mixture at 11.3 T, based on the spin rotation parameter data of Ishimoto et al 17 Consequently, we infer that the value of T a ϭ13 mK reported in our earlier publication 5 is largely due to finite-size effects. By contrast, for the experiment of Wei et al, 16 the value of parameter b L was 7.4 ϫ10 4 , so we expect the effect of restricted diffusion to be relatively small. Using the data of Candela et al, 7 the corresponding apparent anisotropy temperature would be 3 mK in pure 3 He at 8 T, which is much smaller than the value of 16 mK reported in Ref.…”
Section: Comment On Existing Nmr Datamentioning
confidence: 78%
See 1 more Smart Citation